Developing a Marketing Strategy for Private Colleges in 2026 - Erlan Gantira; Widia Ningsih (Interdiciplinary Journal and Hummanity (INJURITY), 2025)
Competition among private colleges in attracting new students has continued to intensify along with the increasing number of higher education institutions and changes in the behavior of younger generations in the digital era. These conditions require universities to develop marketing strategies that are more adaptive, innovative, and oriented toward the needs of prospective students. This article aims to analyze the marketing strategies of private higher education institutions in 2026 through approaches such as institutional positioning, the utilization of digital media, target audience identification, the development of relationships with the community, and the organization of campus events as promotional media.This study employs a qualitative descriptive method using a library research approach through the analysis of various theories of higher education marketing, findings from previous studies, and the phenomena of higher education marketing in the digital era. The findings indicate that marketing strategies for private universities should not rely solely on digital promotion, but also need to be supported by institutional differentiation, experiential marketing, the strengthening of academic reputation, alumni engagement, high-quality services, and campus activities capable of creating positive experiences for prospective students. In addition, the utilization of digital technology and data analytics has become an important factor in understanding prospective students’ behavior and improving the effectiveness of marketing communication. Through integrated and adaptive marketing strategies, private higher education institutions can enhance their competitiveness while strengthening their institutional image amid increasingly competitive higher education environments.